Nature-Inspired Structures Applied in Heat Transfer Enhancement and Drag Reduction - Zhu, Zhangyu; Li, Juan; Peng, Hao; Liu, Dongren (Micromachines (Basel), 2021)
Heat exchangers are general equipment for energy exchange in the industrial field. Enhancing the heat transfer of a heat exchanger with low pump energy consumption is beneficial to the maximum utilization of energy. The optimization design for enhanced heat transfer structure is an effective method to improve the heat transfer coefficient. Present research shows that the biomimetic structures applied in different equipment could enhance heat transfer and reduce flow resistance significantly. Firstly, six biomimetic structures including the fractal-tree-like structure, conical column structure, hybrid wetting structure, scale structure, concave-convex structure and superhydrophobic micro-nano structure were summarized in this paper. The biomimetic structure characteristics and heat transfer enhancement and drag reduction mechanisms were analyzed. Secondly, four processing methods including photolithography, nanoimprinting, femtosecond laser processing and 3D printing were introduced as the reference of biomimetic structure machining. Finally, according to the systemic summary of the research review, the prospect of biomimetic heat transfer structure optimization was proposed.